GAME EDUKASI BAHASA INGGRIS MENGGUNAKAN METODE GOAL DIRECTED DESIGN - Evanny Christianisa; Rosa Delima; Theresia Herlina R. (Universitas Kristen Duta Wacana, 2015)
Education game is a media used as a learning tool. In this research, we built a learning application of animal and fruit names vocabulary in English. Users of the application are 4 to 6 years old children. The purpose of this research is to build an application that can improve children’s ability to remember and enrich their Vocabulary. For the user interface design we implement Goal Directed Design Method. This Method consists of eight main stages, which is research, modeling, requirements, definition, framework definition, refinement, and support. Participants of this research were 18 children aged 4 to 6 years. Based of the evaluation of the application, all participants are able to increase their ability to remember animal and fruit names by about 10%.